Aggressive Angiomyxoma of the Cervix: A Unique Entity - Siwatch, Sujata; Kundu, Reetu; Takkar, Navneet (Global Journal of Medical and Clinical Case Reports, 2014)
Introduction: Aggressive angiomyxoma is a mesenchymal tumour which presents rarely; usually in women in reproductive age group, as a mass in the pelvic tissue. Only exceptionally, has it been seen to originate from the uterus and cervix. Methods: We present a case of a 23-year-old woman who complained about abdominal pain and excessive vaginal bleeding three days after a spontaneous abortion. Examination revealed a large polyp arising from the cervix. Histopathologic examination of the polypectomy specimen revealed an aggressive angiomyxoma of the cervix. Immunohistochemistry was performed and the tumour was immunopositive for vimentin, desmin and smooth muscle actin. Management options are discussed, in light of need of fertility conservation. Result: Aggressive angiomyxoma can originate from the mesenchymal tissue of the cervix. Conclusions: Treatment may be individualized with surgery and hormonal treatment. Long term follow up is recommended.